Arrhythmogenic Cardiomyopathy: Molecular Insights for Improved Therapeutic Design - Stevens, Tyler L. (J Cardiovasc Dev Dis, 2020)
Arrhythmogenic cardiomyopathy (ACM) is an inherited disorder characterized by structural and electrical cardiac abnormalities, including myocardial fibro-fatty replacement. Its pathological ventricular substrate predisposes subjects to an increased risk of sudden cardiac death (SCD). ACM is a notorious cause of SCD in young athletes, and exercise has been documented to accelerate its progression. Although the genetic culprits are not exclusively limited to the intercalated disc, the majority of ACM-linked variants reside within desmosomal genes and are transmitted via Mendelian inheritance patterns; however, penetrance is highly variable. Its natural history features an initial “concealed phase” that results in patients being vulnerable to malignant arrhythmias prior to the onset of structural changes. Lack of effective therapies that target its pathophysiology renders management of patients challenging due to its progressive nature, and has highlighted a critical need to improve our understanding of its underlying mechanistic basis. In vitro and in vivo studies have begun to unravel the molecular consequences associated with disease causing variants, including altered Wnt/β-catenin signaling. Characterization of ACM mouse models has facilitated the evaluation of new therapeutic approaches. Improved molecular insight into the condition promises to usher in novel forms of therapy that will lead to improved care at the clinical bedside.